2017
DOI: 10.1016/j.carres.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the LPS O-chain from Fusobacterium nucleatum strain 10953, containing sialic acid

Abstract: Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. Recently, it has been gaining attention as a potential causative agent for colorectal cancer and is strongly linked with pregnancy complications including pre-term and still births. Little is known about virulence factors of this organism and thus we have initiated studies to examine the bacterial surface glycochemistry. Consistent with a recent paper suggesting that F. nucleatum strain 10593 can synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…animalis ATCC 51191. Among F. nucleatum strains there is a high variability of O‐antigen structures characterized to date [6,13–19] . According to the Bacterial Carbohydrate Structure Database, [25,27] F. nucleatum ATCC 51191 LPS trisaccharide represents a novel O‐antigen structure for bacterial LPS.…”
Section: Discussionmentioning
confidence: 99%
“…animalis ATCC 51191. Among F. nucleatum strains there is a high variability of O‐antigen structures characterized to date [6,13–19] . According to the Bacterial Carbohydrate Structure Database, [25,27] F. nucleatum ATCC 51191 LPS trisaccharide represents a novel O‐antigen structure for bacterial LPS.…”
Section: Discussionmentioning
confidence: 99%
“…LPS comprises four structural domains, which might function in bacterial attachment to the host 38,39 . It has been shown that sialic acid in LPSs can inhibit the immunological response by binding to specific receptors, escape host immune surveillance, and facilitate the formation of biofilms 40 . Interestingly, we found that more than one species was responsible for the observed alteration of microbial function.…”
Section: Discussionmentioning
confidence: 71%
“…38,39 It has been shown that sialic acid in LPSs can inhibit the immunological response by binding to specific receptors, escape host immune surveillance, and facilitate the formation of biofilms. 40 Interestingly, we found that more than one species was responsible for the observed alteration of microbial function. Taking LPSs as an example, up to six species were found to contribute to the enriched LPS function in CRC.…”
Section: Discussionmentioning
confidence: 79%
“…We and others have shown that many strains of F. nucleatum express surface sialic acid, 55,56 and specifically in the case of F. nucleatum strains, sialic acid is a component of the lipopolysaccharide O-chain. 55 It is predicted that sialic acid after entering the cell via NanOU/NanT transporter is converted to GlcNAc-6P by the action of NanA, NanK and NanE enzymes encoded by the sialic acid utilization Nan operon 47 (Figure 3). GlcNAc-6P can either enter the energy utilization pathway, or be shunted into a peptidoglycan biosynthetic pathway as depicted in Figure 3.…”
Section: Scavenging On Host Sialic Acid For Survival In Biofilmsmentioning
confidence: 84%
“…Not only epithelial cells, but other bacteria with which T. forsythia is known to interact, such as F. nucleatum can provide sialic acid. We and others have shown that many strains of F. nucleatum express surface sialic acid, and specifically in the case of F. nucleatum strains, sialic acid is a component of the lipopolysaccharide O‐chain . It is predicted that sialic acid after entering the cell via NanOU/NanT transporter is converted to GlcNAc‐6P by the action of NanA, NanK and NanE enzymes encoded by the sialic acid utilization Nan operon (Figure ).…”
Section: Scavenging On Host Sialic Acid For Survival In Biofilmsmentioning
confidence: 98%